PENGARUH KOMITMEN ORGANISASI, KOMITMEN PROFESIONAL DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Kantor Akuntan Publik di Semarang) - Dista Amalia Arifah; Candra Romadhon (Conference In Business, Accounting, And Management (CBAM), 2015)
The purpose of this study was to examine whether organisation commitment, professional commitment and leadership style had influenced toward job satisfaction with motivation as intervening variable. This research used primary data, auditor on puclic accountant sector in Semarang as population. Using a convenience sampling method, 43 quessioner. The data was analyzed by multiple regression. All data variable meet with validity test, reliability test, normality also classical assumption. The result showed that organization commitment, profesional commitment, leadership style and motivation influenced significantly on job satisfaction. On the other hand organization commitment, profesional commitment and leadership style had influenced on job satisfaction did not through motivation as intevening variable. Keywords : organization committment, profesional committment, leadership style, motivation, job satisfaction